Is nail-plate docking worth the effort? A biomechanical analysis of docking a plate and a nail in peri-implant femur fractures - Bremer, Justus; Heilig, Maximilian; Heilig, Philipp; Hölscher-Doht, Stefanie; Meffert, Rainer H.; Jordan, Martin C. (Frontiers in Bioengineering and Biotechnology, 2024)
The ideal treatment of peri-implant femur fractures (PIFFs) remains unclear due to the thin clinical and biomechanical evidence concerning the most suitable form of osteosynthesis. The purpose of the present study was thus to determine the biomechanical stability that results from combining a cephalomedullary nail and a plate for proximal PIFFs, especially when the nail-plate docking technique is applied.Methods: 24 PIFFs were simulated in both 12 foam and 12 composite specimens and were stabilized via a combination of a cephalomedullary nail and a plate. The control group (n = 6) had a nail and a plate without a connection, while the intervention group (n = 6) had a screw that connected the plate with the interlocking screw hole of the nail, thereby creating a nail-plate docking system. The specimens were evaluated under axial and torsional loading using a material-testing machine and a 3D metrology system. Results: The data regarding stiffness, failure load, and failure displacement showed significantly higher stability for specimens without nail-plate docking. For docked specimens, a non-significant trend toward a higher resistance to torque was observed. Both techniques displayed no significant difference in fracture gap displacement or total displacement.The present study suggests that nail-plate docking of a cephalomedullary nail, and a plate significantly decreases the stiffness and stability of osteosynthesis under axial loading. However, there seems to be a tendency toward higher resistance to torque. Therefore, surgeons should consider this technique if higher torsional stability is necessary, and they should decide against it, if axial stability is preferred.